Вдосконалення методики активного аудиту служби Active Directory Windows Server - Вакуленко, Д. В.; Добринін, І. С. (ХНУРЕ, 2023)
Active Directory is currently the most popular solution for building domain networks. This report is aimed to cover the questions related to the unique development of the methodology for active audit of Active Directory service using the newest Windows Server 2019 update. The ISO family of standards, the COBIT 2019 standard and pentest methodologies, which eventually became a kind of basis for this development, were also reviewed. This work can be used during the audit of Windows Server from the perspective of a penetration tester, to improve the security of the company that uses the domain controller.
Keywords: активний аудит; кібербезпека